Variação no conteúdo de DNA, na proporção de CG e em genes de terpeno sintase de espécies de Psidium e relação com a produção e composição de óleos essenciais - Silva, Matheus Alves (2020)
The genus Psidium belonging to the family Myrtaceae has great representativity, containing approximately 100 species. About 61 occur in Brazil and are distributed in all Brazilian regions, in the most varied phytogeographical domains. The guava (P. guajav